FACTORS AFFECTING FINANCIAL PERFORMANCE COMPANY: STUDY FOR BISNIS27 LISTED COMPANY AT INDONESIA STOCK EXCHANGE - Vita Marina, Diana; Winoto, Agustinus (Journal of Applied Finance and Accounting, 2024)
The research objective is to measure whether company size, industry sensitivity, government ownership, liquidity and company age affect the financial performance of company that listed in Index BISNIS-27 between year 2021-2023. Data that use is secondary data and purposive sampling method. Data collected from list of company Index BISNIS-27 that listed on Indonesia Stock Exchange and consistently listed between 2021-2023. Index BISNIS-27 is an index that evaluated by the price performance from 27 shares that determined by the Indonesian Business Index Committee (idx.co.id). The data collected were processed using SmartPLS 4. From the analysis results liquidity (current ratio) has p values 0.044 (less than 0.05) and company size has p values 0.025 (less than 0.05). Meanwhile, the industry sensitivity has p values 0.158 (more than 0.05), government ownership has p values 0.392 (more than 0.05), and company age has p values 0.145 (more than 0.05). The research concludes that liquidity (current ratio), and company size positively and significantly affect on a company financial performance. Meanwhile, the industry sensitivity, government ownership, and company age positively and insignificantly affect on a company financial performance.